2022
DOI: 10.1136/thoraxjnl-2021-218629
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between asthma and severe COVID-19: a national cohort study

Abstract: BackgroundWe aimed to determine whether children and adults with poorly controlled or more severe asthma have greater risk of hospitalisation and/or death from COVID-19.MethodsWe used individual-level data from the Office for National Statistics Public Health Data Asset, based on the 2011 census in England, and the General Practice Extraction Service data for pandemic planning and research linked to death registration records and Hospital Episode Statistics admission data. Adults were followed from 1 January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 19 publications
(35 reference statements)
1
34
2
2
Order By: Relevance
“…For example, treatment of these cultures with IL-13, a type 2 cytokine that is known to play a role in allergy and asthma pathogenesis in humans along with IL-4 and IL-5, induces goblet cell hyperplasia and mucus hypersecretion, replicating the tissue landscape in an asthmatic airway (Ordoñez et al ., 2001; Rogers, 2002; Kanoh, Tanabe and Rubin, 2011; Everman, Rios and Seibold, 2019). The impact of IL-13 treatment on HCoV replication is of particular interest, as most clinical association studies have shown that individuals with allergic asthma (mediated by type 2 cytokines such as IL-13) are either less prone to developing severe COVID-19 or are at no increased risk than the general population despite airway remodeling induced by asthma (Chhiba et al ., 2020; Green et al ., 2021; Dolby et al ., 2022). Two recent studies treated primary bronchial epithelial cells with IL-13 and showed that this treatment resulted in significant decreases in SARS-CoV-2 replication (Bonser et al ., 2022; Morrison et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, treatment of these cultures with IL-13, a type 2 cytokine that is known to play a role in allergy and asthma pathogenesis in humans along with IL-4 and IL-5, induces goblet cell hyperplasia and mucus hypersecretion, replicating the tissue landscape in an asthmatic airway (Ordoñez et al ., 2001; Rogers, 2002; Kanoh, Tanabe and Rubin, 2011; Everman, Rios and Seibold, 2019). The impact of IL-13 treatment on HCoV replication is of particular interest, as most clinical association studies have shown that individuals with allergic asthma (mediated by type 2 cytokines such as IL-13) are either less prone to developing severe COVID-19 or are at no increased risk than the general population despite airway remodeling induced by asthma (Chhiba et al ., 2020; Green et al ., 2021; Dolby et al ., 2022). Two recent studies treated primary bronchial epithelial cells with IL-13 and showed that this treatment resulted in significant decreases in SARS-CoV-2 replication (Bonser et al ., 2022; Morrison et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It appears that our patient never developed COVID-19, and we do not know if SARS-CoV-2 infection would have been able to trigger EGPA in this case. At the beginning of the COVID-19 pandemic, great concern rose over possible greater severity of infection in patients with asthma, but this was not confirmed in practice [ 27 , 28 , 29 ] and apart from rare reports there is no strong evidence suggesting that COVID-19 can be an EGPA trigger in patients with asthma. It is impossible to know if our patient would otherwise have developed EGPA at some point in his life, but our case report may suggest that caution should be paid with the administration of additional vaccine doses in individuals who experience an increase in IMD severity that persists over time following previous vaccine shots.…”
Section: Discussionmentioning
confidence: 99%
“…16,17) However, others reported that children (12-17 years) with asthma are at higher risk of requiring hospitalization for COVID-19. 18) It has also reported that COVID-19 patients aged ≥16 years with asthma are more likely to require critical care (adjusted odds ratio [aOR], 1.20; 95% confidence interval [CI], 1.05-1.37), noninvasive ventilation (aOR, 1.36; 95% CI, 1.18-1.57), and oxygen supplementation (aOR, 1.33; 95% CI, 1.17-1.50) than those without asthma. 19) These findings suggest that the association between asthma and severe COVID-19 is complex and that the characteristics of the study population require consideration to reveal the potential connections.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Some studies have reported that asthma is not a risk factor for severe COVID-19 ( Table 2 ) [ 16 , 17 ]. However, others reported that children (12–17 years) with asthma are at higher risk of requiring hospitalization for COVID-19 [ 18 ]. It has also reported that COVID-19 patients aged ≥16 years with asthma are more likely to require critical care (adjusted odds ratio [aOR], 1.20; 95% confidence interval [CI], 1.05–1.37), noninvasive ventilation (aOR, 1.36; 95% CI, 1.18–1.57), and oxygen supplementation (aOR, 1.33; 95% CI, 1.17–1.50) than those without asthma [ 19 ].…”
Section: Asthmamentioning
confidence: 99%